2008
DOI: 10.1080/10253890701850239
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational effects of cocaine on maternal aggressive behavior and brain oxytocin in rat dams

Abstract: Gestational cocaine treatment results in significantly increased maternal aggression towards an intruder by postpartum day six, while acute postpartum treatment dose dependently decreases maternal aggressive (MA) behavior. Both increased and decreased aggression in the cocainetreated dams are correlated with either decreased or increased levels of oxytocin in the amygdala, respectively. The current study was an effort to determine whether the effect of gestational cocaine on maternal aggression is transient or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 61 publications
8
60
0
Order By: Relevance
“…Chronic cocaine treatment has been shown to increase maternal aggression during the postpartum period (Johns et al 1994(Johns et al , 1998a, while acute treatment has been shown to decrease it (Johns et al 1994(Johns et al , 1998bMcMurray et al 2008). Here, we found that repeated cocaine exposure increased aggressive behavior in ovariectomized and sham-operated virgin females.…”
Section: Effects Of Cocaine On Female Mandarin Volessupporting
confidence: 58%
“…Chronic cocaine treatment has been shown to increase maternal aggression during the postpartum period (Johns et al 1994(Johns et al , 1998a, while acute treatment has been shown to decrease it (Johns et al 1994(Johns et al , 1998bMcMurray et al 2008). Here, we found that repeated cocaine exposure increased aggressive behavior in ovariectomized and sham-operated virgin females.…”
Section: Effects Of Cocaine On Female Mandarin Volessupporting
confidence: 58%
“…It has been attributed to the effect of the cocaine in the levels of oxytocin in the post-partum period (Heyser, Molina and Spear, 1992;McMurray et al, 2008). These studies have been replicated in humans, for those women that consumed cocaine during their pregnancy showed higher levels of aggression towards their babies in comparison with the mothers of the control group.…”
Section: Alcohol Consumption and Other Abuse Substancessupporting
confidence: 57%
“…Effects on MB wane as the postpartum period progresses and there is increasing distance from the cocaine exposure (Johns et al, 2005a; Heyser et al, 1992). CC typically increases postpartum maternal aggression (MA) towards a submissive intruder by postpartum day six (PPD6) (Johns et al, 1994; Lubin et al, 2003; McMurray et al, 2008b). Conversely, AC postpartum treatment reduces MA, leaving pups defenseless during an intruder session (Nelson et al, 1998a; McMurray et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…CC typically increases postpartum maternal aggression (MA) towards a submissive intruder by postpartum day six (PPD6) (Johns et al, 1994; Lubin et al, 2003; McMurray et al, 2008b). Conversely, AC postpartum treatment reduces MA, leaving pups defenseless during an intruder session (Nelson et al, 1998a; McMurray et al, 2008b). Many of the effects of cocaine treatment during or following gestation have been associated with Oxt system dysregulation in brain regions relevant to MB and MA in rats (Johns et al, 1997a; Nelson et al, 1998a; Johns et al, 1998; Vernotica et al, 1996; 1999; Lubin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%